Didaktik in Stücken - Messmer, Roland (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Stories bring up what gets lost in the confusion of teaching. These stories are crucial for professional ac-tion in the classroom. Didactics in Pieces shows how working on and with stories can create units of meaning so that the uncer-tainty of teaching is used as an occasion for reflection. Didactics in Pieces shows how didactic knowledge can be developed from narrative texts. Didactics in Pieces is therefore mainly concerned with the how and less with the why of didactic teaching. In this sense, Didaktik in Stücken is an inductive teaching of didactics and a toolbox for working with narrative texts.